The Canadian Women’s Heart Health Alliance ATLAS on the Epidemiology, Diagnosis, and Management of Cardiovascular Disease in Women — Chapter 9: Summary of Current Status, Challenges, Opportunities, and Recommendations - Sharon L. Mulvagh, MD, FRCPC, FACC, FASE, FAHA; Tracey J.F. Colella, RN, PhD; Martha Gulati, MD, MS; Rebecca Crosier, MD; Saleema Allana, RN, PhD; Varinder Kaur Randhawa, MD, PhD; Jill Bruneau, PhD, RN; Christine Pacheco, MD; Shahin Jaffer, MD, MHSc, FRCPC; Lisa Cotie, PhD; Emma Mensour; Marie-Annick Clavel, PhD; et al. (CJC Open, 2024)
This final chapter of the Canadian Women’s Heart Health Alliance “ATLAS on the Epidemiology, Diagnosis, and Management of Cardiovascular Disease in Women” presents ATLAS highlights from the perspective of current status, challenges, and opportunities in cardiovascular care for women. We conclude with 12 specific recommendations for actionable next steps to further the existing progress that has been made in addressing these knowledge gaps by tackling the remaining outstanding disparities in women’s cardiovascular care, with the goal to improve outcomes for women in Canada. Résumé: Dans ce chapitre final de l’ATLAS sur l’épidémiologie, le diagnostic et la prise en charge de la maladie cardiovasculaire chez les femmes de l’Alliance canadienne de santé cardiaque pour les femmes, nous présentons les points saillants de l’ATLAS au sujet de l’état actuel des soins cardiovasculaires offerts aux femmes, ainsi que des défis et des occasions dans ce domaine. Nous concluons par 12 recommandations concrètes sur les prochaines étapes à entreprendre pour donner suite aux progrès déjà réalisés afin de combler les lacunes dans les connaissances, en s’attaquant aux disparités qui subsistent dans les soins cardiovasculaires prodigués aux femmes, dans le but d’améliorer les résultats de santé des femmes au Canada.